Local Geomorphological Gradients and Land Use Patterns Play Key Role on the Soil Bacterial Community Diversity and Dynamics in the Highly Endemic Indigenous Afrotemperate Coastal Scarp Forest Biome - Ogola, Henry Joseph Oduor; Selvarajan, Ramganesh; Tekere, Memory (Frontiers in Microbiology, 2021)
Southern Afro-temperate forests are small multi-layered and highly fragmented biodiversity rich biomes that supports unique flora and fauna endemism. However, little is known about the microbial community and their contribution to these ecosystems. In this study, high throughput sequencing analysis was used to investigate the soil bacterial community structure and function, and understand the effect of local topography/geomorphological formations and land use patterns on a coastal scarp forest. Soil samples were collected from three forest topography sites: upper (steeper gradients, 30-55o; open canopy cover, <30%), mid (less steep, 15-30o; continuous forest canopy, >80%) and lower (flatter gradient, <15o; open canopy cover, 20-65%), and from the adjacent sugarcane farms. Results indicated that forest soils were dominated by members of phyla Proteobacteria (mainly members of α-proteobacteria), Actinobacteria, Acidobacteria, Firmicutes and Planctomycetes, while Actinobacteria and to a lesser extent β-proteobacteria and γ-proteobacteria dominated sugarcane farm soils. The core bacterial community clustered by habitat (forest vs sugarcane farm) and differed significantly between the forest topography sites. The Rhizobiales (genera Variibacter, Bradyrhizibium and unclassified Rhizobiales) and Rhodospirallales (unclassified Rhodospirillum DA111) were more abundant in forest mid and lower topographies. Steeper forest topography (forest_upper) characterized by the highly leached sandy/stony acidic soils, low in organic nutrients (C and N) and plant densities correlated to significant reduction of bacterial diversity and richness, associating significantly with members of order Burkholderiales (Burkholderia-Paraburkholderia, Delftia, and Massilia) as the key indicator taxa. In contrast, changes in the total nitrogen (TN), organic matter (SOM) and high acidity (low pH) significantly influenced bacterial community structure in sugarcane farm soils, with genus Acidothermus (Frankiales) and uncultured Solirubrobacterales YNFP111 (Solirubrobacterales) were the most abundant indicator taxa . Availability of soil nutrients (TN and SOM) was the strongest driver of metabolic functions related to C fixation and metabolism, N and S cycling; these processes being significantly abundant in forest than sugarcane farm soils. Overall, these results revealed that the local topographical/geomorphological gradients and sugarcane farming affect both soil characteristics and forest vegetation (canopy coverage), that indirectly drives the structure and composition of bacterial communities in scarp forest soils.